Trello Virtual Learning and Its Effect on Students’ Critical Thinking Skills in Essay Writing - Mohan Rathakrishnan, Manvender Kaur, Hisyham Zakaria ,Arumugam Raman (International Journal of Advanced Science and Technology, 2020)
The research was conducted to study “Trello”virtual learning to enhance the critical thinking skills among upper secondary students in writing essays and to identify the level of students’ critical thinking through different gender. Most Form Four students have problems in identifying, understanding and integrating the context of the Malay subjects, which is different from what they have learned from previous subjects in lower secondary. The methodology of this study involves quantitative and qualitative research. The sample was selected from Form Four students in two schools within the northern part of Kedah. An after-only research design was utilised in this study. Eighty students from both schools will be involved in the sample of this study. School X will be selected as the experimental group (writing essays using Trello online platform to identify the idea of ​​writing and the description of the maturity and interaction with peers) and school Z as the control group (writing essays using the conventional method of teaching) in Form Four Malay Language. Each selected student has the same capabilities and qualifications as they were chosen after PT3 or Grade 3 Assessment. Researchers used a set of inferential statistics, t-test analysis. There are different types of t-tests, depending on the sample type and the variability of the variables according to the two groups. Research results show that the critical thinking levels of students who use Trello online discussion are slightly better in essay writing compared to students who do not use Trello. Trello online discussion is expected to help students improve their ability to convey higher-order thinking skill